Analisis Pengaruh Halal Brand Awareness, Viral Marketing dan Service Quality Terhadap Brand Image Coffee Shop di Kota Tasikmalaya - Alwan Azis Mustafa; Adhi Prapaskah Hartadi; Cupian Cupian (STIKes Ibnu Sina Ajibarang, 2025)
Coffee shops have grown rapidly as part of a modern lifestyle, particularly in Tasikmalaya City, which is known as a city of Islamic boarding schools with a majority Muslim population and high religiosity. However, there are still many coffee shops in the city that have not been registered for halal certification, leading to confusion among Muslim consumers regarding what is permissible to consume according to sharia law. This issue highlights the need for clear information on halal products to help Muslim consumers make informed choices when visiting coffee shops. Therefore, the purpose of this study is to examine the effect of halal brand awareness, viral marketing, and service quality on the brand image of coffee shops in Tasikmalaya City. The study uses a quantitative approach with a survey method. Data were collected through questionnaires, which were distributed both online and directly to Muslim generation Z coffee shop consumers in Tasikmalaya City, with a total of 131 respondents. The sampling method used was purposive sampling. Data analysis was conducted using the Structural Equation Modeling (SEM) technique with the help of SmartPLS 4 software. The results of the study indicate that halal brand awareness, viral marketing, and service quality have a positive and significant effect on the brand image of coffee shops in Tasikmalaya City. These findings suggest that improving halal brand awareness, leveraging viral marketing strategies, and providing excellent service quality are essential for enhancing the brand image and attracting more Muslim consumers to coffee shops in the city.